E-Learning Management Practices and Student Achievement in Islamic Education in the Digital Era - Ferdinan ferdinan (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to examine the relationship between students’perceived e-learning management practices and students’ achievement in Islamic Religious Education (IRE) in an Islamic boarding school, and to estimate the extent to which e-learning management contributes to variations in IRE achievement.   Methodology: A predictive correlational (explanatory survey) design was applied to 45 Grade XI students using total sampling. Data were collected using a 15-item Likert questionnaire, supported by observation and official documentation of IRE academic records. Data were processed using descriptive statistics and simple linear regression in IBM SPSS Statistics version 26, with a t-test for coefficient significance at α = 0.05.   Main Findings: Students reported high perceived e-learning management (M = 64.20; SD = 26.89) and high IRE achievement (M = 91.80; SD = 5.039; Min = 83; Max = 98). Regression results showed a significant positive association (B = 0.086; SE = 0.025; Beta = 0.459; t = 3.395; p = 0.001) with R = 0.459 and R² = 0.211, indicating that e-learning management accounted for 21.1% of the variance in IRE achievement.   Novelty/Originality of this study: This study advances existing evidence by examining e-learning as a measurable management-related construct associated with IRE achievement in an Islamic boarding school context. It provides practical insight for administrators to strengthen platform support, monitoring routines, and teacher facilitation to improve digital IRE learning outcomes.